The Use of Articles in Toponymic Phrases in English and Albanian - Marko Kukić; Anđela Marković (Društvene i Humanističke Studije)
This paper examines noun phrases functioning as toponyms in English and Albanian, with a particular focus on their degree of definiteness. By exploring the role of articles in achieving definiteness, the study conducts a contrastive analysis of article usage in these two languages. Given that the article is a complex grammatical category, acquired progressively across different linguistic levels, the paper aims to analyze and compare its role, grammatical function, and form, as well as the rules governing its use in toponymic phrases. Starting from the premise that English and Albanian belong to distinct language families, the study utilizes a corpus of sentence sets to investigate which linguistic factors influence the use of articles with geographical names. The findings reveal that, in Albanian, syntactic norms ‒ the function of toponymic phrases within sentences ‒ and pragmatic considerations play a significant role in determining article usage. In contrast, article application in English is shaped by the interplay of multiple linguistic disciplines, with semantics exerting the greatest influence. However, syntax also can play a role in dictating usage rules, while pragmatics and historical linguistics provide insights into exceptions and irregularities. This comparative study highlights the differing linguistic mechanisms that govern definiteness in English and Albanian toponymic noun phrases, offering a deeper understanding of article usage across these two languages.